Penerapan Kecerdasan Buatan dalam Perlindungan Nasabah pada Layanan Perusahaan Asuransi: Tinjauan Hukum dan Pertanggungjawaban - Dina Alya Maisan; Naufal Hanif Fakhri Wibowo; Tuktara Sumarno Putri; Suryo Satrio Saryanto; Muhaimin Fachrul Feryansyah; Rahma Ernanda Tiavani (Journal of Legal, Political, and Humanistic Inquiry, 2025)
The integration of artificial intelligence into insurance services has reshaped the operational structure of the insurance industry through automated risk assessment, premium calculation, and claims processing. These technological advancements enhance efficiency and decision accuracy but simultaneously raise legal challenges related to personal data protection and accountability toward policyholders. This study analyzes the application of artificial intelligence in insurance services from a normative legal perspective, focusing on data protection and legal responsibility. By employing statutory and conceptual approaches, the research examines regulations governing personal data protection, insurance supervision, and digital financial services, alongside legal doctrines on liability and consumer protection. The analysis reveals that the use of artificial intelligence increases the vulnerability of policyholders when data security, transparency, and regulatory oversight are insufficient. Legal responsibility remains centered on insurance companies as system controllers, despite the autonomous nature of algorithmic decision-making. Strengthening regulatory harmonization, supervisory mechanisms, and legal awareness is essential to ensure effective protection of policyholders’ rights and sustainable development of insurance services in the digital era.